Piero Sepulcri (1899-1980) and malaria eradication in Veneto - Lazzarini, Luca; Giordani, Maria Teresa; Manfrin, Vinicio (Le infezioni in medicina, 2019)
Piero Sepulcri may be considered the antimalaria pioneer in the Italian region of Veneto during the 20th century. Through his activity with the Regional Antimalarial Institute he made a major contribution to one of the most important successes of medicine in the 20th century: malaria eradication in Italy. His writings on the activity of the Antimalarial Institute display the phases of eradication. In the first period antimalarial drugs were used to cure infected patients and as prophylaxis against infection. In the second period, eradication of vectors permitted the lack of transmission and consequent eradication of malarial disease. The history of malaria eradication in Italy is of the utmost importance because it established a series of steps to be taken against any transmittable disease that could return and spread once again in Italy or elsewhere. Keywords: malaria, anopheles, prophylaxis, treatment, history, Veneto.